Factors associated with the intention to practise family planning among antenatal women with risk of gestational diabetes mellitus in Klang Health District: a cross-sectional study - Baharuddin, Siti Athirah; Sumsusdin, Mohd Hafiz; Dong, Ley Na; Lim, Pei Sean; Hameed, Nasrinsa Shahul; Md Nawawi, Nor Aliah; Affan, Nur Akmal; Kanapathy, Shanmuga Kritika; Mohamad, Fadzilah; Cheong, Ai Theng (Academy of Family Physicians of Malaysia, 2024)
Introduction: Family planning (FP) is important in reducing maternal morbidity and mortality as well as foetal and neonatal complications. This study aimed to determine the intention to practise FP among antenatal women at risk of gestational diabetes mellitus (GDM) in the Klang Health District and its associated factors. Methods: A cross-sectional study was conducted at four government health clinics in the Klang Health District. A total of 431 antenatal women at risk of GDM were recruited using systematic random sampling. A validated self-administered questionnaire was used to assess knowledge, attitude, previous practice and intention to use FP after delivery. Multiple logistic regression (MLR) was used to determine the factors associated with the intention to practise FP. Results: Approximately 64.7% (n=279) of the respondents intended to practise FP. MLR showed that the factors associated with the intention to practise FP were Malay ethnicity (odds ratio [OR]=3.319, 95% confidence interval [CI]=1.431–7.697), low income (OR=2.174, 95% CI=1.317–3.588), good knowledge (OR=2.591, 95% CI=1.008–6.174) and good previous practice (OR=3.956, 95% CI=1.428–9.052). Conclusion: The prevalence of the intention to practise FP among antenatal women at risk of GDM was 64.7%. Malay antenatal women from low-income households with good knowledge and previous practice were more likely to have the intention to practise FP after delivery. Thus, interventions targeted at non-Malay women and measures to improve their knowledge might help improve the intention and uptake of FP among these women.